FK866 reduces axon pathology in in vitro and in vivo models of Huntington’s disease and Alzheimer’s disease and attenuates behavioral abnormalities - Othman, Othman Ahmad (2016)
Among its various biological functions, NAD metabolism regulates axon degeneration, which is an early and often causative event in a variety of neurodegenerative diseases including Huntington’s disease (HD) and Alzheimer’s disease (AD). Our research group previously found that reducing the levels of the NAD precursor nicotinamide mononucleotide (NMN) pharmacologically with the NMN-synthesizing enzyme nicotinamide phosphoribosyl transferase (NAMPT) inhibitor FK866 or genetically by expressing the bacterial enzyme NMN deamidase in mammalian neurons remarkably reduces axon degeneration after acute injury. Here, we asked whether FK866 could also improve axonal pathology and behavioral symptoms in in vitro and in vivo models of HD and AD, and compared its effect to that of memantine, an N-methyl-D-aspartate receptor (NMDAR) antagonist with a well-defined neuroprotective action. An inducible PC12 cell line expressing wild type (Q21 PC12 cells) and HD-associated mutant Huntingtin (mHTT) protein (Q72 PC12 cells) was used as an in vitromodel of HD, while amyloid-beta (Aβ) treatment in mouse cortical neurons was used to mimic AD-associated Aβ toxicity in vitro. We found that FK866 in combination with nicotinic acid (NA) that maintains NAD levels while reducing NMN levels significantly rescued axonal pathology and ameliorated nuclear morphology in HD and AD cellular models. NMN added together with FK866/NA significantly reverted FK866-mediated axonal protection. In contrast, memantine improved nuclear abnormalities while showing no effect in the axonal compartment. The similarity between our result in cellular HD and Aβtoxicity models and that observed in a model of Wallerian degeneration (Di Stefano et al. 2014) suggests that FK866-induced neuroprotection is linked to the reduction in NMN production and it is not due to off-target effects of FK866 and underlines shared mechanisms between axon pathology in disease and that after an acute injure. I tested FK866 efficacy in vivo using HdhQ140 mice, a knock-in mouse model of HD, and APPswe/PS1dE9 mice, a transgenic mouse model of AD, crossed with the yellow fluorescent protein (YFP)-H transgenic mouse line. In these mice, YFP protein is expressed in restricted subsets of neurons, allowing imaging of individual neuronal structures. The point here is to see at which neuronal compartment pathology begins. Consistent with previous reports (Adalbert et al. 2009; Marangoni et al. 2014), I found that axonal swellings and dystrophies appear early in HdhQ140/YFP-H mice and in APPswe/PS1dE9/YFP-H mice and were the major structural abnormalities detected in these mice at the time-point considered. FK866 in combination with NA significantly decreased the number of axonal swellings detected in HdhQ140/YFP-H mice and that of axonal dystrophies detected in APPswe/PS1dE9/YFP-H mice without causing any alteration in nuclear or dendritic morphology of these mice. In addition, FK866 significantly reduced APPswe/PS1dE9/YFP-H mice hyperactivity, a known behavioural abnormality in these mice. On the other hand, memantine significantlyrestored the reduction in locomotor activity of HdhQ140/YFP-Hmiceand improved the sensorimotor gating abnormalities of APPswe/PS1dE9/YFP-H mice. Our results underlines potential mechanistic similarities between axonal abnormalities induced by mHTT and Aβin vitroand in in vivo and those after acute injury, and they highlight the possible therapeutic value of limiting NMN levels with FK866.